(3ahGFO WHjIs
(3ChdgG (B:s
(3GdMeO ddg , aGFOI ddQjM GdeYchS , JCNP ChbjI hTb hChbjg s
(3BNQgG (B:s
(3efg CjVkG ddUaQGA GdJi ai GdjOjf h GdQLdjf hTbhbgeG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B173 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1121(3O(B) s
Keywords: (3GdWHs